2018
DOI: 10.3389/fmicb.2018.02058
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Response of Corynebacterium glutamicum to Increasingly Nutrient-Rich Growth Conditions

Abstract: To ensure economic competitiveness, bioprocesses should achieve maximum productivities enabled by high growth rates (μ) and equally high substrate consumption rates (qS) as a prerequisite of sufficient carbon-to-product conversion. Both traits were investigated and improved via bioprocess engineering approaches studying the industrial work horse Corynebacterium glutamicum. Standard minimal medium CGXII with glucose as sole carbon source was supplemented with complex brain-heart-infusion (BHI) or amino acid (AA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 78 publications
2
22
0
Order By: Relevance
“…Among the most commonly used devices are table-top fermenters, baffled or non-baffled cultivation asks and miniature bioreactor systems (MBRs) in micro-well plate formats. 3,4 Apart from their sizes, the most striking differences between these macrouidic devices are the throughput capacities, costs of maintenance and operating principles. Cultivation asks and MBRs are mainly operated in batch mode.…”
Section: Macrouidic Cultivation Systemsmentioning
confidence: 99%
“…Among the most commonly used devices are table-top fermenters, baffled or non-baffled cultivation asks and miniature bioreactor systems (MBRs) in micro-well plate formats. 3,4 Apart from their sizes, the most striking differences between these macrouidic devices are the throughput capacities, costs of maintenance and operating principles. Cultivation asks and MBRs are mainly operated in batch mode.…”
Section: Macrouidic Cultivation Systemsmentioning
confidence: 99%
“…The metabolic flux map of Figure 8 mirrors cellular efforts to provide sufficient metabolic precursors, reduction equivalents, and ATP at a growth rate of 0.4 h –1 that represents growth conditions typically observed under non-limited batch conditions ( Blombach et al, 2013 ; Grünberger et al, 2013 ; Graf et al, 2018 ; Haas et al, 2019 ). Apparently, the central metabolism of C. glutamicum serves the pivotal need of precursor supply for biomass formation which is mirrored by the strong activity of glycolysis fueling the TCA cycle.…”
Section: Discussionmentioning
confidence: 99%
“…However, a putative drawback lies in the somewhat reduced growth rates compared to other hosts such as Escherichia coli . With about 0.4 h –1 wild-type (WT) C. glutamicum shows only moderate growth in synthetic media in classical batch cultivations ( Blombach et al, 2013 ; Grünberger et al, 2013 ; Graf et al, 2018 ; Haas et al, 2019 ) compared to about 0.7–0.8 h –1 maximum growth rate of other prokaryotes such as E. coli , 1.7 h –1 for the putative future competitors Vibrio natriegens ( Hoffart et al, 2017 ) and Geobacillus LC300 with 2.15 h –1 ( Long et al, 2017 ). Relatively low space-time yields compared to other hosts may be the consequence.…”
Section: Introductionmentioning
confidence: 99%
“…Strain SA-7 carrying an empty plasmid produced 10.9 ± 0.92 g/L of shikimic acid (Figure 4, orange bar) with a yield of 0.22 g shikimate/g-glucose, about two-fold higher than SA-7 cultivated in CGXII minimal medium. Graf et al reported that ATP and NADPH generation was enhanced in nutrient-rich medium (Graf et al, 2018), contributing to increased shikimic acid production. SA-7 overexpressing aroG and aroB strains produced 10.9 ± 0.38 g/L and 10.6 ± 0.36 g/L of shikimic acid in CGXIIY medium (Figure 4, orange bars), respectively, almost the same as SA-7 carrying an empty vector.…”
Section: Construction Of C Glutamicum Strains With Integrated Arog Amentioning
confidence: 99%